Links between precipitation patterns over eastern tropical South America and productivity in the western tropical South Atlantic Ocean during the last deglacial - Martins, Alisson K.; Kochhann, Karlos Guilherme Diemer; Chiessi, Cristiano Mazur; Bauersachs, Thorsten; Zardin, Tamires N.; Campos, Marília C.; Krahl, Guilherme; Souza, Lais Viena de; Crivellari, Stefano; Bahr, André; Kuhnert, Henning; Schwark, Lorenz; et al. (Quaternary international, 2023)
The possibility of a collapse (or marked weakening) of the Atlantic Meridional Overturning Circulation (AMOC) within a few centuries boosted the interest of the scientific community on the responses of different compartments of the climate system to past AMOC collapses (or marked weakening). The most recent examples of such periods are Heinrich Stadial 1 (HS1,18-15 ka BP; near-collapsed AMOC) and the Younger Dryas (YD, 12.9-11.7 ka BP; markedly weakened AMOC). Here, we present data from elemental ratios, spectral reflectance, organic biomarkers, sea surface temperatures and planktonic foraminiferal assemblage from two marine sediment cores recovered from the western tropical South Atlantic Ocean spanning the last ca. 20 kyr. The recovered sediments record the responses of eastern tropical South American hydroclimate, western tropical South Atlantic productivity and sea surface temperatures to changes in AMOC strength associated with HS1 and the YD. Our data show that both periods were characterized by wetter conditions over eastern tropical South America associated with increased continental runoff compared to the Last Glacial Maximum. High sea surface temperatures during HS1 and the YD are in line with marked AMOC decreases that led to heat accumulation in the surface layer of the western South Atlantic Ocean, facilitating increased precipitation over eastern tropical South America. Our data demonstrate for the first time that intense runoff during HS1, and hence nutrient transfer to the ocean, affected the pelagic ecosystem, likely increasing primary productivity in the otherwise oligotrophic western tropical South Atlantic Ocean. Our study demonstrates a tight coupling between marine and terrestrial processes in the eastern South American realm during periods of strong climate instability.